Other-Emptiness in the Work of an Unknown Mystic Illuminating the Path to Freedom by Jamyang Sarma Sherab Özer - Georgios Halkias; Tsering Drukgyel (Religions)
In this article, we investigate the previously unstudied life and works of the late-12th/early-13th century Tibetan polymath Jamyang Sarma Sherab Özer (‘Jam dbyang gsar ma shes rab ‘od zer), an important Buddhist master in the Dro lineage of the Kālacakra Tantra. We will focus on his unique syncretic work, Illuminating the Path to Freedom (Thar lam sgron me), and provide an overview of his surviving literary output. Jamyang Sarma predates Dölpopa Sherab Gyeltsen (Dol po pa shes rab rgyal mtshan, 1292–1361) in the use of the term ‘other-emptiness’, or ‘extrinsic emptiness’ (gzhan stong), in his writings, as opposed to the well-known view of Madhyamaka on ‘self-emptiness’ (rang stong). While conventional historiography has predominantly attributed the earliest systematic deployment of the technical term gzhan stong to Dölpopa, whose writings indeed represent the most comprehensive theoretical exposition within the Jonang tradition, current philological evidence suggests more complex lines of transmission through earlier Tibetan masters. This essay will shed new light on this issue by looking into Jamyang Sarma’s Illuminating the Path to Freedom.